2005
DOI: 10.1081/cbi-200053477
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Rhythm of Core Temperature: Origin and some Implications for Exercise Performance

Abstract: This review first examines reliable and convenient ways of measuring core temperature for studying the circadian rhythm, concluding that measurements of rectal and gut temperature fulfil these requirements, but that insulated axilla temperature does not. The origin of the circadian rhythm of core temperature is mainly due to circadian changes in the rate of loss of heat through the extremities, mediated by vasodilatation of the cutaneous vasculature. Difficulties arise when the rhythm of core temperature is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(145 citation statements)
references
References 39 publications
7
133
1
4
Order By: Relevance
“…Nonetheless, when comparing our predefined analytical limits (>0.2ºC) and effect size between session 1 and 4, meaningful reductions of 0.4% were present in the SDHA group similar to that reported elsewhere (Sunderland et al, 2008;Petersen et al, 2010). Similar results were present in T repeak reductions of 0.7% within the SDHA but not TDHA group, as comparison between sessions 1 to 4 are contributed by circadian fluctuations in T re (Waterhouse et al, 2005). No change in T re occurred in the CON group.…”
Section: 2supporting
confidence: 85%
“…Nonetheless, when comparing our predefined analytical limits (>0.2ºC) and effect size between session 1 and 4, meaningful reductions of 0.4% were present in the SDHA group similar to that reported elsewhere (Sunderland et al, 2008;Petersen et al, 2010). Similar results were present in T repeak reductions of 0.7% within the SDHA but not TDHA group, as comparison between sessions 1 to 4 are contributed by circadian fluctuations in T re (Waterhouse et al, 2005). No change in T re occurred in the CON group.…”
Section: 2supporting
confidence: 85%
“…It is well known that temperature follows a circadian pattern with higher values during daytime than during night-time. 23 Acker et al observed a circadian pattern of temperature at onset of labour, although at a slightly lower level, probably because they measured temperature orally. 24 In our study, admission temperature and mean temperature followed a circadian pattern.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Although rectal measurement has some inconvenience, we decided on this method as it is generally considered to be gold standard for clinical temperature measurement. 23,35,37 Conclusions At the beginning of labour, temperature was 37.1°C (2SD 0.7). Temperature increased slowly during labour and was 37.4°C (2SD 1.2) after 22 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The suprachiasmatic nuclei drives circadian rhythms in physiological processes, which are synchronized to the outside world mainly by the solar light-dark cycle. Core body temperature (CBT) has been investigated as a robust and convenient circadian marker rhythm in humans (4,64,67). However, the circadian rhythm of CBT is more than a marker (17,63); thermoregulatory changes are intimately coupled to sleepiness and sleep induction (see below).…”
mentioning
confidence: 99%